Network-driven discovery yields new insight into Shox2-dependent cardiac rhythm control - Hoffmann, Sandra; Mellein, Stefanie; Rädecke, Kristin; Rheinert, David; Diebold, Sabrina; Röth, Ralph; Weiß, Birgit; Granzow, Martin; Niesler, Beate; Griesbeck, Anne; Eckstein, Volker; Zimmermann, Wolfram-Hubertus; et al. (Biochimica et biophysica acta. Gene regulatory mechanisms, 2021)
The homeodomain transcription factor SHOX2 is involved in the development and function of the heart's primary pacemaker, the sinoatrial node (SAN), and has been associated with cardiac conduction-related diseases such as atrial fibrillation and sinus node dysfunction. To shed light on Shox2-dependent genetic processes involved in these diseases, we established a murine embryonic stem cell (ESC) cardiac differentiation model to investigate Shox2 pathways in SAN-like cardiomyocytes. Differential RNA-seq-based expression profiling of Shox2+/+ and Shox2−/− ESCs revealed 94 dysregulated transcripts in Shox2−/− ESC-derived SAN-like cells. Of these, 15 putative Shox2 target genes were selected for further validation based on comparative expression analysis with SAN- and right atria-enriched genes. Network-based analyses, integrating data from the Mouse Organogenesis Cell Atlas and the Ingenuity pathways, as well as validation in mouse and zebrafish models confirmed a regulatory role for the novel identified Shox2 target genes including Cav1, Fkbp10, Igfbp5, Mcf2l and Nr2f2. Our results indicate that genetic networks involving SHOX2 may contribute to conduction traits through the regulation of these genes.
Gesehen am 10.06.2021